Tiny-Heart: Wearable para alerta de posibilidad de cardiopatía congénita (2024)
After a process of observation and contact with healthcare professionals who have been present in disconnected healthcare environments in Colombia, we focused our attention on the processes and methods used by healthcare providers in these regions. This observation led us to emphasize the importance of early detection means for rapidly escalating health conditions, which are directly affected by the disconnection from the healthcare system. Therefore, we decided to concentrate our study on congenital heart diseases in infants and their early detection to improve access to treatment with minimal permanent consequences for the patient. We formulated the following need: A way to expedite the detection process of congenital heart diseases (CHD) in remote or low-resource areas to enhance survival rates in neonates by saving time in case escalation. To address this need, we have proposed the development of a low-cost wearable device that does not rely on a permanent internet connection and services, which can alert healthcare providers in low-resource regions about the need for case escalation.